Las tensiones en el ethos político de los adventistas en Bucaramanga, Colombia (1928-1948) - Lancheros, Jonathan Ortega (Revista cultura y religión, 2023)
The article examines the prescriptions and political practices developed by converts from the Seventh-day Adventist Church (IASD) in Bucaramanga, Colombia, within the framework of the Liberal Republic (1930-1946), historical period marked by the expansion of civil liberties and the institutionalization of Protestant denominations. Points that these Adventists assumed as political ethos characterized by the tension between their demands for religious freedom and their antagonism towards other religious expressions. The historical reconstruction of the relations established with the local community, the Catholic Church and other heterodox groups are proposed as axes of analysis; as well as the examination of political-citizen training devices deployed in temple and school. The theoretical-methodological approach is in the sociology of Protestantism by Jean-Paul Willaime (2005) from two dimensions: a) symbolic, referring to the ways in which parishioners interpret and communicate sensitivities in the sacred and profane spheres; b) institutional, evidenced in the organization of religious group structures in their interaction with their social context. The sources used include church manuals, doctrine books, administrative documents, press and interviews.